2016
DOI: 10.7554/elife.18426
|View full text |Cite
|
Sign up to set email alerts
|

Similar GABAA receptor subunit composition in somatic and axon initial segment synapses of hippocampal pyramidal cells

Abstract: Hippocampal pyramidal cells (PCs) express many GABAAR subunit types and receive GABAergic inputs from distinct interneurons. Previous experiments revealed input-specific differences in α1 and α2 subunit densities in perisomatic synapses, suggesting distinct IPSC decay kinetics. However, IPSC decays evoked by axo-axonic, parvalbumin- or cholecystokinin-expressing basket cells were found to be similar. Using replica immunogold labeling, here we show that all CA1 PC somatic and AIS synapses contain the α1, α2, β1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 49 publications
(73 reference statements)
8
16
0
Order By: Relevance
“…This is consistent with previous reports demonstrating that α 1 containing receptors are functionally localized to distal dendritic synapses whereas α 2 containing GABA A receptors preferentially mediate perisomatic phasic inhibition (Prenosil et al 2006). Using high resolution EM freeze fracture immunolabelling, it was recently demonstrated that synapses on the soma and axon initial segment (AIS) contain receptors with both α 1 and α 2 subunits (Kerti-Szigeti & Nusser, 2016). Moreover, prior work had suggested a remarkable input specific molecular segregation of GABA A receptor subunits.…”
Section: Gaba a Receptors Containing α 2 Subunits Have A Privileged Rsupporting
confidence: 90%
See 2 more Smart Citations
“…This is consistent with previous reports demonstrating that α 1 containing receptors are functionally localized to distal dendritic synapses whereas α 2 containing GABA A receptors preferentially mediate perisomatic phasic inhibition (Prenosil et al 2006). Using high resolution EM freeze fracture immunolabelling, it was recently demonstrated that synapses on the soma and axon initial segment (AIS) contain receptors with both α 1 and α 2 subunits (Kerti-Szigeti & Nusser, 2016). Moreover, prior work had suggested a remarkable input specific molecular segregation of GABA A receptor subunits.…”
Section: Gaba a Receptors Containing α 2 Subunits Have A Privileged Rsupporting
confidence: 90%
“…Rather distinct synapses onto the soma and AIS from PV and CCK interneurons have similar subunit compositions where both α 1 and α 2 subunits are present in most labelled synapses (Kasugai et al . ; Kerti‐Szigeti & Nusser, ). Our functional results using the selective pharmacological profile of AZD7325 are consistent with inhibitory synapses localized close to the soma containing receptors with the α 2 subunit.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4) it is likely that the MsrB3-ir CA1 pyramidal somatic puncta associate with somatic synapses. CA1 pyramidal neurons have somatic synapses with presynaptic zones belonging to inhibitory interneurons [20]. Somatic inhibitory synapses in CA1 pyramidal neurons are characterized by the excitatory activity-related rapid structural plasticity resulting in synapse enlargement and increased efficiency of somatic inhibition[21].…”
Section: Discussionmentioning
confidence: 99%
“…Both the α1 and α2 subunits are found in GABAA receptors in the AIS (51, 52). In addition, in layers 2–3 of monkey PFC the expression of GABAA α1 mRNA increases and that of α2 decreases across postnatal development (53).…”
Section: Discussionmentioning
confidence: 99%